Mitochondrial DNA mutation load in a family with the m.8344A>G point mutation and lipomas: a case study. Issue 12 (2nd November 2017) - Jeppesen, Tina Dysgaard; Al‐Hashimi, Noor; Duno, Morten; Wibrand, Flemming; Andersen, Grete; Vissing, John
Key Clinical Message: Studies have shown that difference in mtDNA mutation load among tissues is a result of postnatal modification. We present five family members with the m.8344A>G with variable phenotypes but uniform intrapersonal distribution of mutation load, indicating that there is no postnatal modification of mtDNA mutation load in this genotype. Abstract : Studies have shown that difference in mtDNA mutation load among tissues is a result of postnatal modification. We present five family members with the m.8344A>G with variable phenotypes but uniform intrapersonal distribution of mutation load, indicating that there is no postnatal modification of mtDNA mutation load in this genotype.